Evaluation of six single nucleotide polymorphisms for bovine traceability in the context of the argentine-chinese beef trade - Ripoli, María Verónica (2013)
Genetic traceability refers to methods associated with the identification of animals and their products through DNA characterization of individuals, breeds or species. To trace breeds, it is necessary to define the breed groups to analyze, and the most appropriate molecular marker set. The selection of genetic markers depends on the gene frequency distribution, the genetic distance among breeds and the presence of private alleles. In this study, we assessed six single nucleotide polymorphisms (SNPs) located in the DGAT1, TG, LEP, GH, FABP4 and GnRHR genes, as potential genetic markers to be included into a panel for genetic traceability for the identification of breed origin associated with the bovine beef trade. The results of the genetic characterization of four of the main Chinese cattle populations and of the principal breeds raised in Argentina and in the world (five Bos taurus and two B. indicus) suggest that these SNP markers can be successfully used as a part of an effective traceability system for the identification of cattle breed origin in the context of the Chinese meat imports, and in particular in the Argentine-Chinese beef trade.